The Influence of Green Accounting, Capital Structure and Sustainability Report on Company Value with Financial Distress as an Intervening Variable in Manufacturing Companies in the Food and Beverage Industry Sub-Sector Listed on the Indonesia Stock Exchan - Permata Sari, Lian Undari; Yuliusman, Yuliusman; Mansur, Fitrini (Jurnal Cakrawala Akuntansi, 2025)
The purpose of this study is to determine Green Accounting, Capital Structure and Sustainability Report on Company Value with Financial Distress as an Intervening Variable in Manufacturing Companies in the Food and Beverage Industry Sub-Sector Listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This research method uses descriptive verification through a quantitative approach. The sample in this study was 49 Manufacturing Companies in the Food and Beverage Industry Sub-Sector Listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The analytical tools used in this study are descriptive statistical analysis and inferential statistical analysis using multiple linear regression models with the help of SPSS Version 25. The results of the study indicate that Green Accounting does not have a significant effect on Company Value. Capital Structure has a significant effect on Company Value. Sustainability Report has a significant effect on Company Value. Financial Distress has a significant effect on Company Value. Green Accounting has a significant effect on Company Value with Financial Distress as an intervening variable. Capital Structure does not have a significant effect on Company Value with Financial Distress as an intervening variable. Sustainability Report has a significant effect on Company Value with Financial Distress as an intervening variable. Keywords: Green Accounting, Capital Structure, Sustainability Report, Company Value, Financial Distress